Oleic acid promotes atherosclerosis via multiple pathophysiological mechanisms: a narrative review. Issue 2 (9th June 2022) - Chu, Ting; Yang, Maosheng
Abstract : Abstract: An increasing body of evidence supports the hypothesis that atherosclerosis is caused by multiple factors and mechanisms. A better understanding of the contribution of hypertriglyceridemia or oleic acid to the pathogenesis of atherosclerosis would significantly increase our ability to successfully treat these diseases. We propose that oleic acid promotes atherosclerosis via multiple pathophysiological mechanisms. Here we suggest that (1) atherosclerosis may develop through multiple pathophysiological mechanisms and that this may be a common feature of human diseases; (2) diseases may be the consequence of natural selection or the interaction of internal and external factors; (3) diseases should be recognized with "biological diversity, " and that this concept should be introduced into medical education, clinical treatment, drug research and development, and medical research. The work reported here will benefit a new generation of medical trainees and promote the development of the relevant medical fields.